2010
DOI: 10.1111/j.1467-8624.2010.01433.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Values, and Occupational Interests Among Children, Adolescents, and Adults

Abstract: Work fulfills personal values, perhaps differently for males and females. Explored here was the role values play in shaping occupational interests. Study 1 examined children's, adolescents', and adults' (N = 313) occupational values (regarding money, power, family, altruism), occupational interests, and perceptions of values afforded by traditionally masculine and feminine occupations. Results revealed sex differences in occupational values and interests. Furthermore, participants' values predicted their own i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
168
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(187 citation statements)
references
References 46 publications
11
168
1
7
Order By: Relevance
“…It has been strongly suggested that gender role plays a causal role in determining an individual's occupational interests (Weisgram et al, 2010). Research has shown that males show a greater interest in masculine jobs and females show a greater interest in feminine jobs.…”
Section: Gender and Occupationmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been strongly suggested that gender role plays a causal role in determining an individual's occupational interests (Weisgram et al, 2010). Research has shown that males show a greater interest in masculine jobs and females show a greater interest in feminine jobs.…”
Section: Gender and Occupationmentioning
confidence: 99%
“…Across age groups, females have been shown to prefer female-oriented professions more than boys prefer male-dominated ones (Teig & Susskind, 2008). While males seem to seek out status, primarily money and power (Weisgram et al, 2010;Weisgram et al, 2011), regardless of an occupation's gender role orientation, females eschew status in favor of a female-dominated area. Males, on the other hand, are not as focused on avoiding feminine-typed behaviors and characteristics in terms of activities or occupations (Patterson, 2012).…”
Section: Gender and Occupationmentioning
confidence: 99%
See 3 more Smart Citations